Roof characteristics for integrated solar collection in dwellings of RealEstate developments in Concepción, Chile - Zalamea, Esteban; Garcia Alvarado, Rodrigo (Revista de la Construcción. Journal of Construction, 2014)
This paper presents an analysis of the roofs of recently built singlefamily homes in Concepción, Chile in order to identify their potential for integrated solar energy collection. It seeks to promote the installation of domestic renewable energy systems in the face of growing residential energy consumption. The study comprises 2,139 homes in the district, all of which are part of residential developments built since 2006 (68.28% of total homes built over this period). The houses all have pitched roofs with a mean azimuth of 37.48°. The largest or second largest roof section was identified for each housing model, facing north, east or west with an average area of 33.9 sqm. This roof surface receives a total annual solar radiation of between 954 kWh/sqm and 1,732.8 kW/sqm (depending on size, azimuth and pitch), which, equipped with average-performance integrated photovoltaic panels, could supply a mean value of 6.317.2 kWh/year. This production could fully supply the average household annual electricity consumption, with surplus production either fed into the national grid or contributing to household heating needs. Dual production was also assessed with thermo-photovoltaic hybrid technology that could double useful energy production. Results show that the roof characteristics of new housing are compatible with integrated solar collection.